How did we do? The impact of relative performance feedback on intergroup hostilities - Kevin Bauer (Leibniz Institute for Financial Research SAFE, 2020)
Using a novel experimental design, I test how the exposure to information about a group's relative performance causally affects the members' level of identification and thereby their propensity to harm aliates of comparison groups. I find that both, being informed about a high and poor relative performance of the ingroup similarly fosters identification. Stronger ingroup identification creates increased hostility against the group of comparison. In cases where participants learn about poor relative performance, there appears to be a direct level effect additionally elevating hostile discrimination. My findings shed light on a specific channel through which social media may contribute to intergroup fragmentation and polarization.
Keywords: 330; social identity; relative performance feedback; discrimination; outgroup derogation